Dapagliflozin and metformin sustained release tablet and preparation method thereof
By adding crystal form stabilizer and sustained release materials to dagliflozin metformin sustained release tablets, the problem of poor crystal form stability of dagliflozin was solved, the consistency of the efficacy and the ease of the tablet were achieved, and the preparation process was simplified.
Patent Information
- Application Number
- CN202510189816.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2045-02-20
AI Technical Summary
When dapagliflozin and metformin hydrochloride are present, the crystalline stability of dapagliflozin is poor, resulting in loss of drug efficacy. The compressibility of metformin is poor, making the tablet hardness low and easy to break.
Add crystal form stabilizer and sustained-release material to the dapagliflozin metformin sustained-release tablets. The crystal form stability of dapagliflozin is improved through combination, the amount of sustained-release material is reduced, the sheet weight and sheet volume are reduced, and the preparation process is simplified.
The long-term stability of the dagliflozin crystal form is achieved, the consistency of the efficacy is ensured, the volume and weight of the tablet are reduced, and the preparation process is simplified, which reduces the production cost and difficulty.
Smart Images

Figure CN119656122A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a dapagliflozin metformin sustained-release tablet and also relates to a preparation method of the sustained-release tablet, belonging to the field of pharmaceutical preparations. Background Art
[0002] Diabetes is one of the most common endocrine and metabolic diseases. It is caused by genetic susceptibility and triggered by environmental factors. With the development of social economy, changes in people's lifestyles (increased energy intake and reduced exercise, etc.) and the aging of the population, the incidence of type 2 diabetes has been increasing year by year around the world, showing an epidemic trend. Diabetes has now become the third non-communicable disease that threatens people's health and life after cardiovascular disease and tumors.
[0003] At present, commonly used drugs for the treatment of type 2 diabetes include traditional drugs such as biguanides, sulfonylureas, a-glucosidase inhibitors, thiazolidinediones, and new glucose-lowering drugs such as sodium-glucose symporter-2 (SGLT-2) inhibitors and dipeptidyl peptidase-IV (DDP-IV) inhibitors.
[0004] The molecular formula of metformin hydrochloride is C4H 11 N5·HCl, molecular weight is 165.62. Metformin hydrochloride is a highly soluble, low permeability drug of BCS III class. It mainly acts on extra-islet tissues, inhibits intestinal absorption of glucose, increases the utilization of glucose by peripheral tissues, and reduces hepatic gluconeogenesis, thereby achieving the purpose of lowering blood sugar. Since metformin hydrochloride has a significant hypoglycemic effect, does not cause hypoglycemia, and can significantly reduce postprandial hyperglycemia, it is suitable for patients with type 2 diabetes and is a first-line drug for the treatment of type 2 diabetes; at the same time, it can also improve insulin resistance, etc., so it is widely used in clinical practice.
[0005] The molecular formula of dapagliflozin is C 21 H 25 ClO6·C3H8O2·H2O, molecular weight is 502.98. Dapagliflozin is a highly soluble, low permeability drug of BCS III class, and is a SGLT-2 inhibitor that reduces the reabsorption of filtered glucose, lowers the renal (glucose) threshold, and increases the excretion of glucose in urine by inhibiting SGLT-2.
[0006] Dapagliflozin and metformin are commonly used drugs for the treatment of chronic diseases. The two can produce synergistic effects, so they are often needed in the form of a compound for clinical use. However, there are the following problems when the two are made into a compound preparation: 1. Dapagliflozin has poor crystal stability, especially in the presence of metformin hydrochloride, which is easy to cause loss of efficacy and affect the clinical effect of medication; 2. Metformin has poor compressibility, and the tablets are low in hardness and easy to break during storage and transportation.
[0007] In order to solve the above problems, some solutions are pointed out in the prior art, such as CN 102711739 B, CN116370430 A, CN 115414347 A, CN 113398097 A, WO 2017 / 114227 A1, CN 115804770 A, etc. In these prior arts, complex micro-pellet coating isolation, double-layer tableting and other technologies are used to improve the crystal stability of dapagliflozin. Although the crystal transformation can be delayed to a certain extent, the micro-pellet coating isolation and double-layer tableting technologies are complex and cumbersome, with a long production cycle and high cost. The drug is slowly released in the body by adding sustained-release materials, but in order to meet the sustained-release requirements, the amount of sustained-release materials used is relatively large, and the volume of a single tablet is large when it is made into a tablet, which is not easy to swallow. In CN 115804770 A, in order to solve the problem that metformin hydrochloride is a crystalline powder with poor compressibility and is prone to fragmentation and unqualified friability during the industrial production process, the compressibility of the particles and the quality of the tablet surface properties are improved by changing the addition method of the binder, the addition method of the filler, and controlling the ratio of co-grinding of metformin hydrochloride and the lubricant or glidant. However, the control points of the process preparation steps are cumbersome, which increases the difficulty of quality assurance and monitoring of industrial on-site production of drugs. For example, the co-crushing process may cause inconsistent losses of two substances with inconsistent adhesion properties in the crushing pretreatment process, thereby affecting the feed ratio, and cannot meet the GMP requirements of drug production well. Summary of the invention
[0008] In view of the deficiencies in the above-mentioned prior art, the present invention provides a dapagliflozin metformin sustained-release tablet, which contains both a crystal stabilizer and a sustained-release material. The combination of the two not only improves the crystal stability of dapagliflozin, making the sustained-release tablet have consistent efficacy throughout the entire effective period, but also reduces the amount of sustained-release material used, reduces the tablet weight and tablet volume while meeting the sustained-release requirements, and is easier to take.
[0009] The specific technical solutions of the present invention are as follows: A dapagliflozin metformin sustained-release tablet comprises a pharmaceutically active ingredient, a crystal stabilizer and a sustained-release material, wherein the pharmaceutically active ingredient is dapagliflozin, metformin or its hydrochloride, and the crystal stabilizer is at least one of sulfoaluminate, hydrotalcite and sucralfate.
[0010] Furthermore, in the sustained-release tablets, the crystal form of dapagliflozin is its propylene glycol monohydrate crystal form.
[0011] Furthermore, the particle size of the crystal stabilizer is preferably controlled to be less than or equal to 30 um at D90.
[0012] Furthermore, the sustained-release material is at least one of hypromellose, sodium carboxymethyl cellulose, methyl cellulose, carbomer, and sodium alginate, preferably a mixture of hypromellose and carbomer, and the mass ratio of hypromellose to carbomer is 1-9:1, for example, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1.
[0013] Preferably, the viscosity of hypromellose is 50,000-300,000 cps, the viscosity of sodium carboxymethylcellulose is 1,000-50,000 cps, and the viscosity of methylcellulose is 1,000-50,000 cps.
[0014] Preferably, the carbomer may be at least one of carbomer 940, carbomer 980, carbomer 934, carbomer 934P, carbomer 941, carbomer 974P, and the like.
[0015] Furthermore, the crystal stabilizer accounts for 5-15% of the total mass of the crystal stabilizer and the sustained-release material, for example, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, and 15%.
[0016] Furthermore, the total content of the crystal stabilizer and the sustained-release material in the sustained-release tablet is 5-20wt%, for example, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, and 20%.
[0017] Preferably, the crystal stabilizer and the sustained-release material are first made into a composite, and then the composite is used to prepare a sustained-release tablet. Compounding the crystal stabilizer and the sustained-release material in advance can make it easier to disperse and mix evenly when preparing the sustained-release tablet, making the performance of the sustained-release tablet more stable. In addition, making the composite in advance can also improve the compressibility and tableting speed of the sustained-release tablet, and a tablet that meets the hardness requirements can be obtained at a lower tableting strength. The finished tablet has a beautiful and smooth surface, reduces energy consumption, and improves efficiency.
[0018] Furthermore, the complex of the crystal stabilizer and the sustained-release material can be obtained by the following method a or method b: Method a. The crystal stabilizer is crushed to a particle size that meets the requirements, and then mixed evenly with the sustained-release material and water to obtain a suspension, and the suspension is spray-dried to obtain a composite; Method b: The crystal stabilizer is crushed to a particle size that meets the requirements, and then mixed with a sustained-release material and water to form a soft material, the soft material is hot-melt extruded to obtain an extrudate, and the extrudate is dried and crushed to obtain a composite.
[0019] Furthermore, the crystal stabilizer is crushed to a particle size D90 of less than or equal to 30 microns, preferably by air flow crushing.
[0020] Further, in method a, the following steps are specifically included: dissolving the sustained-release material in 50-80°C water with a mass of 0.5-10 times the sustained-release material, stirring until dissolved and clarified, then adding crushed crystal stabilizer, stirring and dispersing to obtain a suspension, connecting the suspension to a spray dryer for spray drying to obtain a composite. Specific spray drying parameters can be: inlet air temperature 60-90°C, for example 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C; inlet air flow 3-10m³ / h, for example 3m³ / h, 4m³ / h, 5m³ / h, 6m³ / h, 7m³ / h, 8m³ / h, 9m³ / h, 10m³ / h; liquid inlet speed 10-50HZ, for example 10 HZ, 20HZ, 30 HZ, 40 HZ, 50 HZ; nozzle diameter 0.1-0.5mm, for example 0.1mm, 0.2mm, 0.3mm, 0.4mm, 0.5mm; spray pressure 0.1-1.0MPa, for example 0.1MPa, 0.2MPa, 0.3MPa, 0.4MPa, 0.5MPa, 0.6MPa, 0.7MPa, 0.8MPa, 0.9MPa, 1.0MPa.
[0021] Furthermore, in method b, the following steps are specifically included: uniformly mixing the sustained-release material and the crushed crystal stabilizer, adding water to prepare a soft material with uniform dry and wet properties, adding the soft material to a hot melt extruder for extrusion to obtain an extrudate, drying the extrudate using a fluidized bed, and then crushing it using a hammer mill to obtain a composite.
[0022] Furthermore, the hot melt extruder is a twin-screw type, the extrusion head is an inverted fish scale mesh, the extrusion temperature is 60-90°C, for example, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C; the extrusion speed is 10-30HZ, for example, 10 HZ, 20 HZ, 30 HZ; the mesh aperture of the extrusion head is 0.6-2mm, for example, 0.6mm, 1mm, 1.5mm, 2mm.
[0023] Furthermore, the feed speed of the hammer mill is 10-30HZ, for example, 10 HZ, 20 HZ, 30 HZ; the crushing rotation speed is 3000-20000rpm, for example, 3000rpm, 5000rpm, 8000rpm, 10000rpm, 15000rpm, 20000rpm; the mesh aperture is 0.2-0.6mm, for example, 0.2mm, 0.3mm, 0.4mm, 0.5mm, 0.6mm.
[0024] Furthermore, metformin hydrochloride is also called metformin hydrochloride, and the content of metformin or its hydrochloride in the sustained-release tablet is 50-90wt%, such as 50%, 60%, 70%, 80%, 90%. The content of dapagliflozin in the sustained-release tablet is 0.5-5wt%, such as 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%.
[0025] Furthermore, the sustained-release tablet may also contain at least one of a filler, a disintegrant, a lubricant, and a coating agent.
[0026] Further, the filler can be a filler disclosed in the medical field, such as one or more of corn starch, microcrystalline cellulose, lactose, mannitol, dextrin, sucrose powder, etc. The content of the filler in the sustained-release tablet can be 0-50wt%, such as 0%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%.
[0027] Further, the disintegrant can be a disintegrant disclosed in the medical field, such as one or more of sodium carboxymethyl starch, cross-linked sodium carboxymethyl cellulose, calcium carboxymethyl cellulose, cross-linked polyvinylpyrrolidone, etc. The content of the disintegrant in the sustained-release tablet can be 0.1-5wt%, such as 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%.
[0028] Furthermore, the lubricant can be a lubricant disclosed in the pharmaceutical field, such as one or more of magnesium stearate, talc, stearic acid, etc. The content of the lubricant in the sustained-release tablet can be 0.1-1wt%, such as 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%.
[0029] Furthermore, the coating agent can be a coating agent disclosed in the pharmaceutical field, such as Opadry, E-Color, Oulun, etc. The content of the coating agent in the sustained-release tablet can be 0-3wt%, such as 0%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%.
[0030] Furthermore, in a specific embodiment of the present invention, a specific sustained-release tablet formulation is disclosed, and the weight percentage of each component is as follows: Metformin or its hydrochloride 50%-90%; Dapagliflozin 0.5%-5%; Crystal stabilizer 0.5%-2.5%; Sustained-release material 3%-16%; Filler 0-50%; Disintegrant 0.1%-5%; Lubricant 0.1%-1%.
[0031] The present invention also provides a method for preparing dapagliflozin metformin sustained-release tablets, the method comprising the following steps: A. crushing the crystal stabilizer to a particle size that meets the requirements, and then uniformly mixing it with the sustained-release material and water to obtain a suspension or a soft material, spray drying the suspension or hot-melt extruding the soft material and then drying and crushing it to obtain a composite of the crystal stabilizer and the sustained-release material; B. Wet granulating the complex of the active ingredient of the drug, the crystal stabilizer and the sustained-release material, drying and granulating the obtained wet granules to obtain dry granules, mixing the dry granules with a filler, a disintegrant and a lubricant, and compressing the obtained mixture to obtain tablets; Alternatively, the active pharmaceutical ingredient, the composite of the crystal stabilizer and the sustained-release material, the filler, and the disintegrant are wet-granulated, the wet granules are dried and granulated to obtain dry granules, the dry granules are mixed with a lubricant, and the mixture is compressed to obtain tablets; C. After obtaining the tablets, preferably, the obtained tablets can be further coated to obtain coated tablets.
[0032] The present invention has the following beneficial effects: 1. The present invention adds a crystal stabilizer to the sustained-release tablet to improve the stability of the dapagliflozin propylene glycol monohydrate crystal form, solves the problem of crystal form transformation and poor crystal stability when dapagliflozin and metformin hydrochloride are present, and prolongs the product shelf life. Experimental verification shows that the sustained-release tablet can ensure crystal stability for at least 24 months, and the dapagliflozin crystal form is stable and the efficacy is consistent throughout the entire shelf life, ensuring the effect of clinical medication.
[0033] 2. The present invention uses a crystal stabilizer in combination with a sustained-release material, which reduces the amount of sustained-release material used. With a lower amount of sustained-release material used, the expected sustained-release effect can be achieved, the tablet weight and volume are reduced, and the tablet is easier for patients to take.
[0034] 3. The preparation method of the present invention is simple. Dapagliflozin and metformin or its hydrochloride can be mixed and granulated together in the presence of a crystal stabilizer and a sustained-release material. There is no need for complicated operations such as pellet coating isolation and double-layer tableting, which simplifies the preparation process, reduces production difficulty and cost, and improves production efficiency.
[0035] 4. The present invention preferably prepares a composite material with the crystal stabilizer and the sustained-release material in advance, and then mixes it with other ingredients, which can improve the tabletability of the sample, obtain tablets with higher hardness under lower pressure, reduce die wear during the production process, increase tableting speed, reduce tableting energy consumption, and significantly save energy and increase efficiency.
[0036] 5. The crystal stabilizer of the present invention is selected from inorganic salts with relatively large hardness and brittleness such as sulphoaluminate, hydrotalcite, and sucralfate. The crystal stabilizer is first made into a complex with a sustained-release material with high toughness, which can eliminate the batch differences of the sustained-release material caused by different sources and preparation processes. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is the XRD spectrum of the sample of Example 1 at 0 month.
[0038] Figure 2 This is the XRD pattern of the sample of Example 1 at 24 months.
[0039] Figure 3 This is the XRD spectrum of the sample of Comparative Example 2 at 0 month.
[0040] Figure 4 This is the XRD spectrum of the sample of Comparative Example 2 at 24 months.
[0041] Figure 5 This is a picture of the in vitro release of the sample of Example 1 for 10 hours.
[0042] Figure 6 This is a picture of the in vitro release of the sample of Comparative Example 1 for 10 hours.
[0043] Figure 7 This is a picture of the in vitro release of the sample of Comparative Example 2 for 10 hours. DETAILED DESCRIPTION
[0044] The following is a description of exemplary embodiments of the present invention, including various details of the embodiments of the present invention to aid understanding, which should be considered as merely exemplary. Therefore, it should be appreciated by those of ordinary skill in the art that various changes and modifications may be made to the embodiments described herein without departing from the scope and spirit of the present invention. Likewise, for clarity and simplicity, descriptions of well-known functions, operations, and structures are omitted in the following description.
[0045] Unless otherwise defined, the technical and scientific terms in this specification have the same meaning as those commonly understood by those skilled in the art. Although similar or identical methods and materials as those described herein may be used in experiments or practical applications, the present invention still describes the materials and methods below. In the event of a conflict, the present specification, including definitions, shall prevail.
[0046] Example 1 A dapagliflozin metformin sustained-release tablet, the formula of which is as described in the following table: The method for preparing the sustained-release tablets is as follows: 1. Preparation of a composite of a crystal stabilizer and a sustained-release material: 1.1. Calcium sulphoaluminate was micronized using a jet mill to obtain calcium sulphoaluminate powder. The powder was subjected to dry laser particle size measurement. The test results showed that D50 was 5 μm and D90 was 13 μm.
[0047] 1.2. Mix hydroxypropyl methylcellulose (viscosity 100,000 cps) and carbomer (934P) with purified water of equal mass, then heat to 70°C and stir until the solution is clear. Slowly add the calcium sulfoaluminate powder obtained in 1.1 and stir to disperse evenly to obtain a suspension.
[0048] 1.3. Connect the suspension in 1.2 to a spray dryer and perform spray drying using the following parameters: air inlet temperature 80°C, air inlet flow 5m³ / h, liquid inlet speed 25HZ, nozzle diameter 0.2mm, and liquid spray pressure 0.6MPa to obtain a composite of the crystal stabilizer and the sustained-release material.
[0049] 2. Granulation 2.1. Add metformin hydrochloride, dapagliflozin, and the complex of the crystal stabilizer and sustained-release material prepared in step 1 into a high-efficiency wet granulator, first dry-mix at a stirring speed of 300 rpm for 5 min, add 15 wt % purified water to the dry-mixed material for 2-5 min after the dry-mixing, and wet-mix at 1500 rpm for 3 min to prepare a soft material.
[0050] 2.2. Granulate the soft material using a fast granulator equipped with a 4*4 square screen and square knife to obtain wet granules. Transfer the wet granules to a fluidized bed for drying. The inlet air temperature of the drying bed is 70°C and the air volume is 10m³ / hour. When the moisture content of the granules is less than 5%, stop heating. Granulate the dry granules using a fast granulator equipped with a 2.0mm round screen and round knife to obtain dry granules.
[0051] 2.3. Put the whole dry granules, microcrystalline cellulose, sodium carboxymethyl starch and magnesium stearate into the material tank of a hopper mixer in proportion, and mix at a speed of 15 Hz for 30 minutes to obtain a tablet intermediate.
[0052] 3. According to the weight of a single tablet of 600 mg, use a circular φ8.5mm shallow concave punch for tableting. The tableting pressure is 5-15KN, the tableting speed is 50KT / h, and the hardness of the obtained tablet is 17-18kg.
[0053] Example 2 Dapagliflozin metformin sustained-release tablets were prepared according to the method of Example 1, except that the formula thereof is as described in the following table: Example 3 Dapagliflozin metformin sustained-release tablets were prepared according to the method of Example 1, except that the formula thereof is as described in the following table: Example 4 Dapagliflozin metformin sustained-release tablets were prepared according to the method and formula of Example 1, except that calcium sulfoaluminate was replaced by an equal amount of magnesium hydrotalcite, and the sustained-release material was replaced by an equal amount of carbomer (974P).
[0054] Example 5 Dapagliflozin metformin sustained-release tablets were prepared according to the method and formula of Example 1, except that calcium sulfoaluminate was replaced with an equal amount of sucralfate, and the sustained-release material was replaced with an equal amount of sodium alginate (ultra-high viscosity type II).
[0055] Example 6 Dapagliflozin metformin sustained-release tablets were prepared according to the method of Example 1, except that the total content of the crystal stabilizer and the sustained-release material in the sustained-release tablets was 5 wt %. The formula was as follows: Example 7 Dapagliflozin metformin sustained-release tablets were prepared according to the method of Example 1, except that the total content of the crystal stabilizer and the sustained-release material in the sustained-release tablets was 15.5 wt %. The formula was as follows: Example 8 Dapagliflozin metformin sustained-release tablets were prepared according to the formula of Example 1, except that the crystal stabilizer and the sustained-release material were not prepared into a compound, and the method was as follows: 1. Calcium sulfoaluminate was micronized using a jet mill to obtain calcium sulfoaluminate powder. The powder was subjected to dry laser particle size measurement, which showed that its D50 was 5 μm and D90 was 13 μm.
[0056] 2. Granulation 2.1. Add metformin hydrochloride, dapagliflozin, crystal stabilizer and sustained-release material into a high-efficiency wet granulator in turn, dry-mix at a stirring speed of 300 rpm for 5 min, add 15 wt% purified water to the dry-mixed material for 2-5 min after the dry-mixing, and wet-mix at 1500 rpm for 3 min to prepare a soft material.
[0057] 2.2. Granulate the soft material using a fast granulator equipped with a 4*4 square screen and square knife to obtain wet granules. Transfer the wet granules to a fluidized bed for drying. The inlet air temperature of the drying bed is 70°C and the air volume is 10m³ / hour. When the moisture content of the granules is less than 5%, stop heating. Granulate the dry granules using a fast granulator equipped with a 2.0mm round screen and round knife to obtain dry granules.
[0058] 2.3. Put the whole dry granules, microcrystalline cellulose, sodium carboxymethyl starch and magnesium stearate into the material tank of a hopper mixer in proportion, and mix at a speed of 15 Hz for 30 minutes to obtain a tablet intermediate.
[0059] 4. According to the tablet weight of 600 mg per tablet, use a circular φ8.5mm shallow concave punch for tablet compression. The tablet compression pressure is 20-30KN, the tablet compression speed is 35-45KT / h, and the tablet hardness is 15-17kg.
[0060] Example 9 Dapagliflozin metformin sustained-release tablets were prepared by referring to the formulation and method of Example 1, except that step 1.1 was omitted and calcium sulfoaluminate was not micronized using a jet mill.
[0061] Example 10 Dapagliflozin metformin sustained-release tablets were prepared according to the method of Example 1, except that the formula thereof is as described in the following table: Comparative Example 1 A dapagliflozin metformin sustained-release tablet, the formula of which is as described in the following table: The method for preparing the sustained-release tablets is as follows: 1. Granulation 1.1. Add metformin hydrochloride, dapagliflozin and hypromellose (viscosity 100,000 cps) into a high-efficiency wet granulator in turn, dry-mix at a stirring speed of 300 rpm for 5 min, add 15 wt% purified water to the dry-mixed materials for 2-5 min, and wet-mix at 1500 rpm for 3 min to prepare a soft material.
[0062] 1.2. Granulate the soft material using a fast granulator equipped with a 4*4 square screen and square knife to obtain wet granules. Transfer the wet granules to a fluidized bed for drying. The inlet air temperature of the drying bed is 70°C and the air volume is 10m³ / hour. When the moisture content of the granules is less than 5%, stop heating. Granulate the dry granules using a fast granulator equipped with a 2.0mm round screen and round knife to obtain dry granules.
[0063] 1.3. Put the whole dry granules, microcrystalline cellulose, sodium carboxymethyl starch and magnesium stearate into the material tank of a hopper mixer in proportion, mix at a speed of 15 Hz for 30 minutes to obtain a tablet intermediate.
[0064] 2. According to the tablet weight of 600 mg per tablet, use a circular φ8.5mm shallow concave punch for tableting. The tableting pressure is 45-55KN, the tableting speed is 15KT / h, and the hardness of the obtained tablet is 17-18kg.
[0065] Comparative Example 2 A dapagliflozin metformin sustained-release tablet, the difference being that the formula thereof is as described in the following table: The method for preparing the sustained-release tablets is as follows: 1. Granulation 1.1. Add metformin hydrochloride, dapagliflozin and hypromellose (viscosity 100,000 cps) into a high-efficiency wet granulator in turn, dry-mix at a stirring speed of 300 rpm for 5 min, add 15% purified water to the dry-mixed materials for 2-5 min, and wet-mix at 1500 rpm for 3 min to prepare a soft material.
[0066] 1.2. Granulate the soft material using a fast granulator equipped with a 4*4 square screen and square knife to obtain wet granules. Transfer the wet granules to a fluidized bed for drying. The inlet air temperature of the drying bed is 70°C and the air volume is 10m³ / hour. When the moisture content of the granules is less than 5%, stop heating. Granulate the dry granules using a fast granulator equipped with a 2.0mm round screen and round knife to obtain dry granules.
[0067] 1.3. Put the whole dry granules, microcrystalline cellulose, sodium starch glycolate and magnesium stearate into the material tank of a hopper mixer in proportion, and mix at a speed of 15 Hz for 30 minutes to obtain a tablet intermediate.
[0068] 2. According to the tablet weight of 600 mg per tablet, use a track-type 12*8.5 mm shallow concave punch for tableting. The tableting pressure is 50-65 KN, the tableting speed is 10 KT / h, and the hardness of the obtained tablet is 13-15 kg.
[0069] Comparative Example 3 Dapagliflozin metformin sustained-release tablets were prepared according to the method of Example 3, except that the formula was as shown in the following table: Performance Verification 1. Dapagliflozin stability test 1.1 The sustained-release tablet samples prepared in each embodiment and comparative example were stored at a temperature of 25°C ± 2°C and a relative humidity of 60% ± 10% for 24 months, and the dapagliflozin content and dapagliflozin crystal form in each sustained-release tablet were tested at 0th month, 12th month and 24th month.
[0070] 1.2 The content of dapagliflozin was determined by high performance liquid chromatography (Chinese Pharmacopoeia 2020 Edition, Part IV, General Rules 0512), as follows: According to the amount of 100 mg of dapagliflozin, a sample of sustained-release tablets of each embodiment and comparative example was weighed and placed in a 1000 ml volumetric flask, and about 80 ml of 75 wt % acetonitrile aqueous solution was added. The sample was placed in a water bath at about 55° C. and ultrasonicated for 20 minutes to dissolve the sample. The sample was then cooled, diluted to the scale with 75 wt % acetonitrile aqueous solution, and shaken to obtain a test solution.
[0071] Take an appropriate amount of dapagliflozin standard, weigh it accurately, dissolve it in 75wt% acetonitrile aqueous solution and dilute it quantitatively to make a solution containing 0.1mg per 1ml to obtain a reference solution.
[0072] Chromatographic conditions: octylsilane bonded silica gel was used as the filler (Thermo Betasil C8 250mm×4.6mm); 10mmol / L potassium dihydrogen phosphate buffer (pH adjusted to 3.0±0.05 with phosphoric acid)-methanol-acetonitrile (volume ratio 55:6:39) was used as the mobile phase; the flow rate was 1.2ml per minute; the column temperature was 35℃; the detection wavelength was 290nm; and the injection volume was 10μl.
[0073] Accurately take the test solution and the reference solution, inject them into the liquid chromatograph respectively, and calculate the content of dapagliflozin by peak area according to the external standard method.
[0074] 1.3 The crystalline form of dapagliflozin was determined by X-ray diffraction (XRD), as follows: The sustained-release tablet samples of each embodiment and comparative example were ground into fine powders meeting the requirements of the pharmacopoeia and used as test samples.
[0075] The sample was tested by XRD with an X-ray diffractometer, using Cu target Kα rays as the radiation source, working voltage 40kV, working current 50mA; scanning speed 5° per minute, scanning range 5°-50°; step length 0.02°, counting time 10 seconds per step. By comparing the diffraction peak position, intensity and shape of the sample placed at different times, the change of crystal form is judged. If the diffraction peak position of the sample after 12 months and 24 months is consistent with that of the sample placed for 0 months, and the relative intensity error is within ±5%, it is judged as qualified crystal form, otherwise it is unqualified crystal form.
[0076] 1.4 Experimental Results The changes in the content and crystal form of dapagliflozin in the products prepared in various embodiments and comparative examples at different time periods are shown in Table 1. The XRD patterns of the samples in Embodiment 1 and Comparative Example 2 at 0 months and 24 months are shown in Table 1. Figure 1-Figure 4 shown.
[0077] Table 1 from Figure 1 and Figure 2 It can be seen that the XRD patterns of the sample of Example 1 at 0 months and 24 months are consistent, and the crystal stability is good. Figure 3 and Figure 4 It can be seen that after 24 months of storage, the peak at about 5.4° of the 2θ angle of the sample of Comparative Example 2 disappeared, the peaks at about 44.8°, 48.9°, and 53.6° increased, and the peak intensities at about 17.7° and 22.4° weakened. Moreover, the change amplitude of these peaks exceeded 5%, indicating a large change in the crystal form, which affected the efficacy.
[0078] Combining Table 1 and Figure 1-4 It can be seen that the samples prepared in each embodiment of the present invention meet the requirements of product crystal form within 24 months, and although the content of dapagliflozin shows a downward trend, it is still greater than 95% at the end of 24 months, which can meet the clinical efficacy, and the sample of Example 1 has the best performance. However, the samples of each comparative example all showed unstable crystal form at 24 months, which affected the efficacy.
[0079] 2. Comparison of the tableting conditions and in vitro release of Example 1, Comparative Example 1 and Comparative Example 2 is shown in Table 2 and Figure 5-Figure 7 shown.
[0080] The in vitro release of dapagliflozin was determined according to the dissolution and release test method (Chinese Pharmacopoeia 2020 Edition, Part IV, General Rules, 0931, Method 1), as follows: Using phosphate buffer (pH 6.8 ± 0.05) filtered through a 0.45 μm filter membrane as the dissolution medium, take one sustained-release tablet sample of each embodiment and comparative example, add it to 900 ml of the dissolution medium, rotate at 100 revolutions per minute, use a 20-mesh rotating basket, and operate according to the law. Take 10 ml of the dissolution solution at 2h, 5h, and 10h, respectively, and add the same volume of dissolution medium in time.
[0081] The 2h and 5h dissolution solutions were filtered and used as the test solution for 2h and 5h; the 10h dissolution solution was filtered and diluted with an equal volume of dissolution medium to use as the test solution for 10h.
[0082] Take 17 mg of dapagliflozin standard, weigh accurately, place in a 100 ml volumetric flask, add 5 ml of acetonitrile to dissolve it, then dilute to the scale with dissolution medium, shake well, and use as the reference solution.
[0083] Taking the dissolution medium as the blank control, take each test sample solution and the reference sample solution, and measure the absorbance of each solution at a wavelength of 242 nm according to the UV-visible spectrophotometry (General Rules 0401 of Part IV of the Chinese Pharmacopoeia 2020 Edition), and then calculate the release of dapagliflozin in each sample at different times. Release = the mass of dapagliflozin in the dissolution solution at different time points / the mass of dapagliflozin in the sustained-release tablets * 100%.
[0084] Table 2 It can be clearly seen from the experimental results in Table 2 above that the tableting of Example 1 is faster and more energy-efficient. During the tableting process, the main pressure of Example 1 is only one-fifth of that of Comparative Example 2, and the hardness value of the obtained sample is higher. According to the experience of the die machinery industry, it can be known that the use of the solution of Example 1 can at least extend the die life by more than 3 times and increase the production speed.
[0085] Figure 5-Figure 7 The release of the samples of Example 1 and Comparative Examples 1-2 in vitro for 10 hours is shown. Combining the graph and the release data, it can be seen that the release data of the sample of Example 1 meets the requirements, and the sample at the release end point presents a complete gel-like tablet. The release of the sample of Comparative Example 1 does not meet the requirements, especially the sudden release phenomenon occurs at 5 hours, and the release end point presents a scattered gel-like state and cannot constitute a continuous phase. The release of the sample of Comparative Example 2 meets the requirements, but the end point value is low (this is a common situation for ordinary gel matrix tablets), and the release end point presents a complete gel-like tablet, but the volume is large.
Claims
1. A dapagliflozin metformin sustained-release tablet, characterized in that: The invention comprises a pharmaceutically active ingredient, a crystal stabilizer and a sustained-release material, wherein the pharmaceutically active ingredient is dapagliflozin, metformin or its hydrochloride, and the crystal stabilizer is at least one of sulfoaluminate, hydrotalcite and sucralfate; the crystal form of dapagliflozin is a propylene glycol monohydrate crystal form.
2. The dapagliflozin metformin sustained-release tablets according to claim 1, characterized in that: The particle size of the crystal stabilizer is controlled to be less than or equal to 30um at D90.
3. The dapagliflozin metformin sustained-release tablets according to claim 1, characterized in that: Include at least one of the following conditions: Condition 1: The sustained-release material is at least one of hydroxypropyl methylcellulose, sodium carboxymethyl cellulose, methyl cellulose, carbomer, and sodium alginate; Condition 2: The crystal stabilizer accounts for 5-15% of the total weight of the crystal stabilizer and the sustained-release material; Condition 3: The total content of the crystal stabilizer and the sustained-release material in the sustained-release tablet is 5-20wt%.
4. The dapagliflozin metformin sustained-release tablets according to claim 1, characterized in that: The sustained-release material is a mixture of hypromellose and carbomer.
5. The dapagliflozin metformin sustained-release tablets according to claim 4, characterized in that: The mass ratio of hypromellose to carbomer is 1-9:
1.
6. The dapagliflozin metformin sustained-release tablets according to any one of claims 1 to 5, characterized in that: The crystal stabilizer and the sustained-release material are added to the sustained-release tablet in the form of a complex, and the complex of the crystal stabilizer and the sustained-release material is obtained by the following method a or method b: a. The crystal stabilizer is crushed to a particle size that meets the requirements, and then mixed evenly with the sustained-release material and water, and the resulting suspension is spray-dried to obtain a composite; b. The crystal stabilizer is crushed to a particle size that meets the requirements, and then mixed with a sustained-release material and water to form a soft material, the soft material is hot-melt extruded to obtain an extrudate, and the extrudate is dried and crushed to obtain a composite.
7. The dapagliflozin metformin sustained-release tablets according to any one of claims 1 to 5, characterized in that: The content of metformin or its hydrochloride is 50-90wt%, and the content of dapagliflozin is 0.5-5wt%.
8. The dapagliflozin metformin sustained-release tablets according to any one of claims 1 to 5, characterized in that: The composition further comprises at least one of a filler, a disintegrant, a lubricant and a coating agent.
9. The dapagliflozin metformin sustained-release tablets according to claim 8, characterized in that: Include at least one of the following conditions: Condition 1: The filler is one or more of corn starch, microcrystalline cellulose, lactose, mannitol, dextrin, and sucrose powder; Condition 2: the disintegrant is one or more of sodium carboxymethyl starch, cross-linked sodium carboxymethyl cellulose, calcium carboxymethyl cellulose, and cross-linked polyvinylpyrrolidone; Condition 3: The lubricant is one or more of magnesium stearate, talc, and stearic acid; Condition 4: The content of the filler in the sustained-release tablet is 0-50wt%; Condition 5: The content of disintegrant in the sustained-release tablet is 0.1-5wt%; Condition 6: The content of lubricant in the sustained-release tablet is 0.1-1wt%; Condition 7: The content of the coating agent in the sustained-release tablet is 0-3wt%.
10. A method for preparing the dapagliflozin metformin sustained-release tablets according to any one of claims 1 to 9, characterized in that The following steps are involved: A. crushing the crystal stabilizer to a particle size that meets the requirements, and then uniformly mixing it with the sustained-release material and water to obtain a suspension or a soft material, spray drying the suspension or hot-melt extruding the soft material and then drying and crushing it to obtain a composite of the crystal stabilizer and the sustained-release material; B. Wet granulating the compound of the active pharmaceutical ingredient, the crystal stabilizer and the sustained-release material, drying and granulating the obtained wet granules to obtain dry granules, mixing the dry granules with a filler, a disintegrant and a lubricant, and tableting the obtained mixture to obtain tablets; or, wet granulating the compound of the active pharmaceutical ingredient, the crystal stabilizer and the sustained-release material, a filler and a disintegrant, drying and granulating the obtained wet granules to obtain dry granules, mixing the dry granules with a lubricant, and tableting the obtained mixture to obtain tablets; C. Optionally, the obtained tablets are coated to obtain coated tablets.
Citation Information
Patent Citations
Double-layer tablets
CN102711739B
Dapagliflozin and metformin sustained release preparation and preparation method thereof
CN113398097A
Sustained release tablet as well as preparation method and application thereof
CN115414347A
Pharmaceutical preparation containing metformin hydrochloride and pioglitazone hydrochloride and preparation method thereof
CN115804770A
Dapagliflozin and metformin sustained release tablet and preparation method thereof
CN116370430A